Riad Sattouf's L'Arabe du futur, bodily humour, and a politics of socio-symbolic adolescence. Issue 1 (July 2017) - Still, Edward John
Abstract : This article, focusing in particular on L'Arabe du future, tome 1 (2014), seeks initially to elucidate a humour of childhood and adolescent bodies produced by Riad Sattouf's filmic and comics œuvre, and goes on to explore the reaction of the reader/viewer as a function of his/her bodily memory and of the incongruity-congruity division upon which much of humour studies has been erected. It argues that Sattouf's work produces visceral and emotional reactions that intertwine to evoke an intriguing complexity of amusement. At the same time, it explores the importance of self-representation and personal memory to the production of humour in Sattouf's work and of an unusual proximity to the bodily childhood/adolescent object. This proximity is argued to act as a foundation for a powerful summoning of childhood absurdity in the reader, one that encourages a focus on psychic structures that evoke the Lacanian notions of the Symbolic Order and big Other. Finally, this article argues that Sattouf's evocation of these structures invites the analysis of a psychic link between childhood development and the subjectivities of adult agents in the political frameworks in gestation which he depicts. It thus investigates how Sattouf amusingly evokes the propensity of adults, like children, to become caught up in discourses generated by what Jacques Lacan would refer to as the figure of the big Other. It is ultimately this article's goal to share the power of Sattouf's work to encourage the reader to accept and laugh at his/her own continued imperfect, 'adolescent', state while humbly working to be as sociopolitically adult, or aware, as possible.